DAMPAK PERNIKAHAN USIA DINI PADA KEHAMILAN DI DESA SEJATI KECAMATAN CAMPLONG KABUPATEN SAMPANG - TINTIN Hariyani; Halimatus Sakdiyah (STIKES dan AKZI Karya Husada Kediri, 2022)
Early marriage is a marriage where the age of the spouse is under the stipulation of 19 years. Early marriage is caused by several factors, including education, customs, and culture. Early marriage has a very important negative impact on teenagers and parents. The purpose of this study was to determine the impact of early marriage on pregnancy. This type of research is observational with a descriptive research design. The population of this study was 26 women who married early at the age of 15-19 years. The research sample is as many as 26 people. The sampling technique used is purposive sampling. This research was conducted from August 20, 2021, to September 7, 2021. Data collection used a questionnaire and an MCH handbook. The results of univariate data analysis showed that most of the respondents experienced hyperemesis as many as 10 respondents (38.5%), 11 respondents (42.3%) experienced anemia, and as many as 5 respondents (19.2%) experienced abortions. This shows that women who marry at an early age are at risk of having a negative pregnancy.